DIVISI DAN ALIENASI MASYARAKAT PRIBUMI DALAM KUMPULAN CERPEN SEMUA UNTUK - Al-Khiyyed, Sy. Fatma; Juanda, Juanda; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
Division and Alienation of Indigenous Communities in A Collection Short Story “Semua Untuk Hindia” by Iksaka Banu. This study aims to describe the impact of racial ethnocentrism the form of division and alienation on indigenous peoples in a collection of short stories Semua untuk Hindia by Iksaka Banu. The research method used is descriptive qualitative. Sources of research data were obtained from a collection of short stories, Semua untuk Hindia by Iksaka Banu. Data collection is done by reducing data, presenting data and drawing conclusions. The results of this study reveal the impact of racial ethnocentrism in a collection of short stories including division, in which indigenous people are grouped according to the standards applied by Europeans. Next is alienation, which is indicated by the alienation due to cultural and racial disparities between Europeans and the natives.